The Implementation of One-Stop Integrated Service Policy in Klungkung Regency - Ni Putu Tirka Widanti; Anak Agung Gde Raka; I Made Surya Atmadja (Iapa Proceedings Conference, 2019)
The government of Klungkung Regency is one of the Regencies in Bali that carried out reforms in order to simplify the licensing process by holding one-stop integrated service. The purpose of this study is to determine the implementation of the policy and the inhibiting factors of the one-stop integrated service. Van Horn and Van Meter Theory were used in this research. The research was conducted at the Department of Investment and One-Stop Integrated Services in Klungkung Regency by using a qualitative research method. The result is that the implementation of the policy shows a tendency for increasingly improved attitudes. The inhibiting factor of the implementation of the policy is the different perception between the Department of Investment and the technical team related to the administrative services and the unavailability of a public service mall to facilitate the licensing and non-licensing process. In terms of human resources, the inhibiting factors are related to professionalism, competence, empathy, and ethics. The next problem is the minimal service quality that complicates the process.